The marketisation of higher education - symptoms, controversies, trends - Hanna Hall (Institute of Economic Research (IER), 2017)
Marketisation of higher education accompanying the development of a market economy having expressed, among others, the "imitation" of management models specific to the enterprise sector, an adaptation of the market terminology, changing roles of students and the importance of their satisfaction with the study causes still a lot of controversy in the academic community, dividing it into supporters and opponents of the current process with a strong predominance of the first group. The aim of this article is to present the arguments and opinions of supporters and opponents of the process of marketization of higher education with a particular emphasis on changes in students roles at nowadays universities. In the article the results of desk research as well as the author's own research will be used. Research carried out by the author were of a qualitative nature and were conducted with an application of In depth Interview method because of the need for full and cogent opinions of the respondents. The research was carried out among 16 representatives of Polish universities, i.e. among Deputy Chancellors (for marketing and development of the university) or departments managers responsible for marketing of the university. For the study there were selected two (public and private) colleges of 8 Polish cities that are capitals of provinces or districts. As measuring instruments, the study used an interview scenario with an average degree of standardization and a voice recorder. Interviews were carried out at the premises of the universities, in the period from 2015 - 2016. They lasted between 1-2,5 hours, depending on the degree of involvement of the university in marketing activities. Supporters of marketisation argue that this process will turn universities into more flexible, more efficient and more responsive to the needs of society, the economy, students and parents institutions. Opponents pay attention to the cultural, intellectual and pedagogic consequences of this process. Both groups conclude that there is no turning back from this process and it cannot be avoided.
Keywords: I23; M39; I29; 330; marketisation of higher education; higher education marketing; changes in higher education marketing